Campus Life Services System / Aisyah Hani Ab Aziz - Ab Aziz, Aisyah Hani (2014)
The manual advertising of students' services requires a lot of work, time, energy and money for instance designing a flyer, printing and making copies of it, distributing it or finding a spot to put up the flyers. Thus, this old manual way of advertising must be improvised to create a better and "much efficient way for students to advertise their services. Hence, this Campus Life Services System is developed to provide an amazing way for students to advertise their services for staffs to sign up for the services offered with a much lower fee. In this way, students will not have to spend a lot of time going through the old process of advertising which is inefficient and time consuming. The agile methodology approach is used on the implementation of this system. This system is believed to be very beneficial as it can help staffs to plan their children schedule during the school break, deepen their knowledge or hobby and sharpen their skills in certain activities by attending these services.